Biometry of testicular growth in Konya Merino, Akkaraman and Awassi ram lambs - OZTURK, A.; DAG, B; KESHKIN, I; AKTAS, A H (The Indian Journal of Animal Sciences, 2014)
In this research testicular development of Konya Merino (KM), Akkaraman (AK) and AWassi (A W) ram lambs was investigated for the period of 3-14 months. Diameter (TD) and length (TL) and scrotal circumference (SC) of testis wereevaluated. Least square means at 3 months of age for KM.,AK and AW breeds, respectively, were determined as 1.72. 1.86 and 1.87 cm for TD, 4.17,4.18 'and 4.47 cm for TL and 9.77, 9.38·and 10.22 cm for SC. Developments of TD TL and SC for KM, AK and AW were 167.44%, 145.16% and 167.91%; 144.12%,132.30% and 143.40%; 185.87%. 183.58% and 188.55% respectively. Differences between the averages of breeds for TD. TL and SC were significant (P